Intertwined roles of fluid–solid interactions and macroscopic flow geometry in dynamic wetting of complex fluids - Sudheer M.V.R.; Yadav P.; Thomas B.; Ghosh U.U. (My University, 2025)
Dynamic wetting of complex fluids is an integral component of several industrial operations ranging from surface coatings to the modern 3D printing. This multifaceted interfacial phenomenon has been reviewed in the past decades either from the perspective of the solid or the fluid. However, it is fundamentally governed by the interfacial interactions between the solid and fluid. In this mini-review, we attempt to propose a general framework for studying the contact line dynamics of complex fluids that is inclusive of these interfacial interactions stemming from solid properties, fluid properties and the macroscopic flow geometry. We critically examine two interfacial phenomena involving complex fluids—spreading/wetting of blood and polymers exhibiting rod-climbing to unveil the existing scientific challenges in the domain. © 2022, The Author(s), under exclusive licence to EDP Sciences, Springer-Verlag GmbH Germany, part of Springer Nature.